WORKSHOP CREATIVEPRENEUR TURNING CREATIVITY INTO BUSINESS OPPORTUNITIES - Simatupang, Apriani; Samuel, Sylvia; Arianto, Radityo Fajar; Chrestella, Valentcia Earlene (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
The growth of Indonesia’s creative economy offers significant opportunities for young generations to become entrepreneurs and contribute to the national economy. However, many students still lack the understanding and hands-on experience needed to transform creative ideas into real business opportunities. In response to this, the Faculty of Economics and Business at Universitas Pelita Harapan (UPH FEB) initiated the Creativepreneur Workshop: Turning Creativity into Business Opportunities at Sekolah Dian Harapan (SDH) Makassar. This workshop is designed to introduce the fundamentals of creative entrepreneurship, foster innovative thinking, and provide practical experience through the creation of simple, marketable products. Additionally, it offers insights on leveraging digital technology and social media for marketing while connecting students with experienced creative business practitioners. The program aims to inspire and equip young people to develop a courageous, adaptive, and entrepreneurial mindset that is capable of creating business opportunities from an early stage.